Rapid diagnostics for point-of-care quantification of soluble transferrin receptorResearch in context - Balaji Srinivasan; Julia L. Finkelstein; Dakota O’Dell; David Erickson; Saurabh Mehta (EBioMedicine, 2019)
Background: Iron deficiency (ID) and anaemia are major health concerns, particularly in young children. Screening for ID based on haemoglobin (Hb) concentration alone has been shown to lack sensitivity and specificity. The American Academy of Pediatrics (AAP) recommends soluble transferrin receptor (sTfR) as a promising approach to screen for iron deficiency. However, in most settings, assessment of iron status requires access to centralized laboratories. There is an urgent need for rapid, sensitive, and affordable diagnostics for sTfR at the point-of-care. Methods: An immunochromatographic assay-based point-of-care screening device was developed for rapid quantification of sTfR from a drop of serum within a few minutes. Performance optimization of the assay was done in sTfR-spiked buffer and commercially available sTfR calibrator, followed by a small-scale proof-of-concept validation with archived serum samples. Findings: On preliminary testing with archived serum samples and comparison with Ramco ELISA, a correlation of 0.93 (P < 0.0001) was observed, demonstrating its potential for point-of-care assessment of iron status. Interpretation: The analytical performance of the point-of-care sTfR screening device indicates the potential for application in home-use test kits and field settings, especially in low- and middle-income settings. An added advantage of sTfR quantification in combination with our previously reported serum ferritin diagnostics is in integration of Cook's equation as a quantitative and minimally-invasive indicator of total body iron stores. Fund: Thrasher Research Fund (Early Career Award #13379), NIH R03 EB 023190, NSF grant #1343058, and Nutrition International (project #10-8007-CORNE-01). Keywords: Iron deficiency, Anaemia, Lateral flow immunoassay, Soluble transferrin receptor, Point-of-care testing, Portable diagnostics